Pelatihan Kewirausahaan Sebagai Upaya Literasi Kemandirian Disabilitas Tegal Bahari - Muhammad Arif Budiman Sucipto; Azzah Putri Oktafiani; Melia Erba Robani; Muspiroh; Salma Sholihati; Sinta Nistiana; Rizki Ismayana; Tri Yunita; Tri Winda Handayani; Witdya Amanah Krismonia (CV. Multi Kreasi Media, 2024)
Disability is a condition where a person has limitations in carrying out daily activities due to physical, mental, intellectual or sensory barriers which give rise to negative stigma from society, such as the opinion that people with disabilities are not worthy of receiving a normal education, let alone working like people in general. Society considers that people with disabilities are the same as sick people who need special treatment and must be cared for with full attention. The aim of this training is an effort to support independent literacy aimed at people with disabilities in Tegal Bahari. The method for implementing this community service program is carried out by providing training and entrepreneurial assistance through several programs such as: training in making shibori batik, hydroponics, spinach sticks, making vlogs and bazaar activities. The results of this entrepreneurship training program include developing skills, increasing creativity, increasing self-confidence in social relationships, developing an entrepreneurial spirit and independence in people with maritime disabilities. The conclusion from this community service is that entrepreneurship training can be an effort to develop independence literacy for maritime disabilities.